Assessment of groundwater quality in eastern part of lower vellar basin, cuddalore district, tamilnadu, India - Dushiyanthan, Chinnadurai; Raja Kumar T, Jeyavel; K, Karthikeyan; B, Thiruneelakandan; D, Davidraju; R, Suresh (International Journal of Advanced Geosciences, 2014)
An attempt has been made in this present work to determine the groundwater quality in eastern parts of Lower vellar basin, Cuddalore district. Totally, ten groundwater samples were collected from bore well during premonsoon seasons and analyzed for physicochemical parameters to understand the hydro geochemistry of the water. The analysis results were interpreted with various geochemical diagrams such as Piper trilinear plot and USSL classification and Gibbs diagram. The range of chemical concentration of cations such as Ca, Mg, Na, k and anions like HCO3, Cl, and SO4 are 25.0 to 90.0 mg/l, 20.6 to 117.5 mg/l, 11.9 to 95.0 mg/l, 1 to 130 mg/l and 25 to 197 mg/l, 111.0 to 275.0 mg/l, 0.13 to 0.78mg/l respectively. To understand the geochemical facies interpreted with Piper Trilinear diagram and Gibb’s dia-grams. The graphical interpretation of Piper trilinear diagram shows Ca, Na facies followed by Cl, So4, and HCO3 facies. Similarly, USSL and Gibb’s diagrams represent C3S1 field and considerable number of samples in rock water interaction field. In the present study to under-stand groundwater quality of lower vellar basin.   Keywords: Groundwater, Hydro Geochemistry, Lowervellarbasin, Groundwater Quality, Hydrogeology, Premonsoon.